Strategi Bisnis Primebiz Hotel Surabaya Menghadapi Pandemi Covid-19 - Salim, Michelle Vebby Tanzil; Satrya, I Dewa Gde; Anshori, Mohamad Yusak (JURNAL MASTER PARIWISATA, 2021)
The Covid-19 pandemic has a negative impact on the tourism and hospitality sector, one of which is PrimeBiz Hotel Surabaya (PHS). The lack of income for the hotel forces hotel management to think creatively and make the right decisions to maintain hotel operations. This study aims to describe the strategies that PHS has implemented during the Covid-19 pandemic. The research method was carried out qualitatively, the data were obtained through structured interviews with key informants from management, marketing experts, hospitality experts and PHS consumers. The conclusion of this study are; first, the Covid-19 pandemic makes PHS management have to weigh income and expenditure to be balanced. Second, the marketing strategy implemented by PHS is to maximize the use of social media for all employees. Third, the strategy carried out by PHS is to continue to implement a multitasking system, employees must be able to innovate and make adjustments to conditions that occur in the future. Keywords: business strategy, hotel, Covid-19